BRAIN ABNORMALITIES IN YOUNG ADULTS AT GENETIC RISK FOR AUTOSOMAL DOMINANT ALZHEIMER’S DISEASE: A CROSS-SECTIONAL STUDY - Reiman, Eric M. (2012)
BACKGROUND: We previously detected functional brain imaging abnormalities in young adults at genetic risk for late-onset Alzheimer’s disease (AD). Here, we sought to characterize structural and functional magnetic resonance imaging (MRI), cerebrospinal fluid (CSF), and plasma biomarker abnormalities in young adults at risk for autosomal dominant early-onset AD. Biomarker measurements were characterized and compared in presenilin 1 (PSEN1) E280A mutation carriers and non-carriers from the world’s largest known autosomal dominant early-onset AD kindred, more than two decades before the carriers’ estimated median age of 44 at the onset of mild cognitive impairment (MCI) and before their estimated age of 28 at the onset of amyloid-β (Aβ) plaque deposition. METHODS: Biomarker data for this cross-sectional study were acquired in Antioquia, Colombia between July and August, 2010. Forty-four participants from the Colombian Alzheimer’s Prevention Initiative (API) Registry had structural MRIs, functional MRIs during associative memory encoding/novel viewing and control tasks, and cognitive assessments. They included 20 mutation carriers and 24 non-carriers, who were cognitively normal, 18-26 years old and matched for their gender, age, and educational level. Twenty of the participants, including 10 mutation carriers and 10 non-carriers, had lumbar punctures and venipunctures. Primary outcome measures included task-dependent hippocampal/parahippocampal activations and precuneus/posterior cingulate deactivations, regional gray matter reductions, CSF Aβ(1-42), total tau and phospho-tau(181) levels, and plasma Aβ(1-42) levels and Aβ(1-42)/Aβ(1-40) ratios. Structural and functional MRI data were compared using automated brain mapping algorithms and AD-related search regions. Cognitive and fluid biomarkers were compared using Mann-Whitney tests. FINDINGS: The mutation carrier and non-carrier groups did not differ significantly in their dementia ratings, neuropsychological test scores, or proportion of apolipoprotein E (APOE) ε4 carriers. Compared to the non-carriers, carriers had higher CSF Aβ(1-42) levels (p=0·008), plasma Aβ(1-42) levels (p=0·01), and plasma Aβ(1-42)/Aβ(1-40) ratios (p=0·001), consistent with Aβ(1-42) overproduction. They also had greater hippocampal/parahippocampal activations (as low as p=0·008, after correction for multiple comparisons), less precuneus/posterior cingulate deactivations (as low as p=0·001, after correction), less gray matter in several regions (p-values <0·005, uncorrected, and corrected p=0·008 in the parietal search region), similar to findings in the later preclinical and clinical stages of autosomal dominant and late-onset AD. INTERPRETATION: Young adults at genetic risk for autosomal dominant AD have functional and structural MRI abnormalities, along with CSF and plasma biomarker findings consistent with Aβ(1-42) over-production. While the extent to which the underlying brain changes are progressive or developmental remain to be determined, this study demonstrates the earliest known biomarker changes in cognitively normal people at genetic risk for autosomal dominant AD. FUNDING: Banner Alzheimer’s Foundation, Nomis Foundation, Anonymous Foundation, Forget Me Not Initiative, Boston University Department of Psychology, Colciencias (1115-408-20512, 1115-545-31651), National Institute on Aging (R01 AG031581, P30 AG19610, UO1 AG024904, RO1 AG025526, RF1AG041705), National Institute of Neurological Disorders and Stroke (F31-NS078786) and state of Arizona.